2021
DOI: 10.3390/antibiotics10091032
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Usage and Resistance in Food Animal Production: What Have We Learned from Bangladesh?

Abstract: Irrational and inappropriate use of antibiotics in commercial chicken and aquaculture industries can accelerate the antibiotic resistance process in humans and animals. In Bangladesh, the growing commercial chicken and aquaculture industries are playing significantly important roles in the food value chain. It is necessary to know the antibiotic usage practices and antibiotic resistance in food animal production to design rational policies, guidelines, and interventions. We conducted a narrative review to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“… Sharma et al (2020) investigated antibiotic use and animal health management in smallholder dairy farms in four urban and peri-urban areas of India and found that the knowledge level and practices related to antibiotic use and antimicrobial resistance can potentially increase the risk of resistance antibiotic development and its transfer in the community, which is a major global public health threat. Unregulated or inappropriate antibiotic use in animal farms and using different types of antibiotics at the same time are still common practices in developing countries ( Gebeyehu et al, 2015 ; Chowdhury et al, 2021 ; Geta and Kibret, 2021 ). In a survey of small-scale farms in Thailand, 57.1% of farmers reported the use of antibiotics for prevention ( Lekagul et al, 2020 ).…”
Section: Bacterial Resistance To Antibiotics In Food Animal Farmsmentioning
confidence: 99%
“… Sharma et al (2020) investigated antibiotic use and animal health management in smallholder dairy farms in four urban and peri-urban areas of India and found that the knowledge level and practices related to antibiotic use and antimicrobial resistance can potentially increase the risk of resistance antibiotic development and its transfer in the community, which is a major global public health threat. Unregulated or inappropriate antibiotic use in animal farms and using different types of antibiotics at the same time are still common practices in developing countries ( Gebeyehu et al, 2015 ; Chowdhury et al, 2021 ; Geta and Kibret, 2021 ). In a survey of small-scale farms in Thailand, 57.1% of farmers reported the use of antibiotics for prevention ( Lekagul et al, 2020 ).…”
Section: Bacterial Resistance To Antibiotics In Food Animal Farmsmentioning
confidence: 99%
“…Regulations on antibiotic usage in Bangladesh aquaculture do exist but are very limited. They are poorly implemented due to insufficient monitoring and surveillance, poor institutional resource capacity (in particular staffing), and poor regulatory control on aggressive and irrational marketing. , A 2020 policy from the Government’s Ministry of Fisheries and Livestock banned antibiotic use in food production, with the exception of oxytetracycline and sulfadiazine which are allowed under prescription . In our social data set, only one farmer could name the antibiotics that are approved for aquaculture use, and none of the farmers kept records of drug use.…”
Section: Resultsmentioning
confidence: 99%
“…In low-middle-income countries, antimicrobials are frequently used as prophylactic drugs in animal production. Because of the easy access to these medicines and their non-restricted use, antimicrobial consumption in the animal production system almost double human consumption [ 42 ]. In developing countries unqualified animal healthcare providers play a significant role in this problematic situation [ 42 ].…”
Section: The Issue Of Antimicrobial Resistance In Livestockmentioning
confidence: 99%